2018
DOI: 10.3390/en11071626
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study of the Solar Collection Performance of Liquid-Type Solar Collectors under Various Weather Conditions

Abstract: To design and use a solar heating system properly, it is very important to evaluate the performance of its solar collector. Because the solar collection efficiency of a solar collector depends on the amount of solar radiation, the conditions of the heating medium (e.g., flow rate and inlet temperature), and the outside air temperature, it is necessary to consider the performance of the solar collector in actual weather conditions that are likely to prevail when using the system for heating and hot water. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Choi [9], based on the amount of solar heat collected per unit area for seven regions in Japan, compared the performance of solar collectors for different weather conditions, such as outdoor temperature or amount of solar radiation. He showed that the performance of solar collectors depends on climatic conditions and that it is important to select the right collector for each region through a preliminary analysis in the initial design stage.…”
Section: Introductionmentioning
confidence: 99%
“…Choi [9], based on the amount of solar heat collected per unit area for seven regions in Japan, compared the performance of solar collectors for different weather conditions, such as outdoor temperature or amount of solar radiation. He showed that the performance of solar collectors depends on climatic conditions and that it is important to select the right collector for each region through a preliminary analysis in the initial design stage.…”
Section: Introductionmentioning
confidence: 99%
“…In a study evaluating the performance of liquid-type collectors, Hill and Streed proposed a test method for determining the efficiency of a solar collector [5]. Similarly, Choi measured and compared the performance of various types of collectors [6]. To increase heat collection performance, Minardi and Chuang made and evaluated a flat-plate type collector using a black liquid as a thermal medium [7].…”
Section: Introductionmentioning
confidence: 99%